M protein ectodomain-specific immunity restrains SARS-CoV-2 variants replication - Tang, Yibo; Tang, Kaiming; Hu, Yunqi; Ye, Zi-Wei; Luo, Wanyu; Luo, Cuiting; Cao, Hehe; Wang, Ran; Yue, Xinyu; Liu, Dejian; Liu, Cuicui; Ge, Xingyi; et al. (Frontiers in Immunology, 2024)
The frequent occurrence of mutations in the SARS-CoV-2 Spike (S) protein, with up to dozens of mutations, poses a severe threat to the current efficacy of authorized COVID-19 vaccines. Membrane (M) protein, which is the most abundant viral structural protein, exhibits a high level of amino acid sequence conservation. M protein ectodomain could be recognized by specific antibodies; however, the extent to which it is immunogenic and provides protection remains unclear. Seroconversion rates for ectodomain-specific IgG were observed to be high in both SARS-CoV-2 convalescent patients and individuals immunized with inactivated vaccines. To assess the protective efficacy of the M protein ectodomain-based vaccine, we initially identified a highly immunogenic peptide derived from this ectodomain, named S2M2-30. The mouse serum specific to S2M2-30 showed inhibitory effects on the replication of SARS-CoV-2 variants in vitro. Immunizations of K18-hACE2-transgenic mice with the S2M2-30-keyhole limpet hemocyanin (KLH) vaccine significantly reduced the lung viral load caused by B.1.1.7/Alpha (UK) infection. Further mechanism investigations reveal that serum neutralizing activity, specific T-cell response and Fc-mediated antibody-dependent cellular cytotoxicity (ADCC) correlate with the specific immuno-protection conferred by S2M2-30. The findings of this study suggest that the antibody responses against M protein ectodomain in the population most likely exert a beneficial effect on preventing various SARS-CoV-2 infections.